2012
DOI: 10.1093/rof/rfs009
|View full text |Cite
|
Sign up to set email alerts
|

Market Selection and Welfare in a Multi-asset Economy*

Abstract: We analyze the performance of irrational investors, who mistake expected returns of assets, in a multi-asset economy. Under general conditions, irrational investors are severely punished compared with rational investors, in that their fractions of consumption and wealth decrease quickly. Further, the welfare cost of such underperformance is often high. Our results contrast with previous studies of single-asset economies, which find modest underperformance by irrational investors. In a calibration, we find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…15 See Basak (2005) and the references therein for a discussion of heterogenous beliefs models when the likelihood ratio is driven by Brownian motions and there is e↵ectively only disagreement about means. For details on investors' survival in heterogenous beliefs models see Fedyk, Heyerdahl-Larsen, and Walden (2013) and the references therein. 16 We divide by p 1 to make the inflation disagreement parameter comparable across examples.…”
Section: Theoretical Resultsmentioning
confidence: 99%
“…15 See Basak (2005) and the references therein for a discussion of heterogenous beliefs models when the likelihood ratio is driven by Brownian motions and there is e↵ectively only disagreement about means. For details on investors' survival in heterogenous beliefs models see Fedyk, Heyerdahl-Larsen, and Walden (2013) and the references therein. 16 We divide by p 1 to make the inflation disagreement parameter comparable across examples.…”
Section: Theoretical Resultsmentioning
confidence: 99%
“…The shortcut taken in this paper is to assume a finite horizon economy under which both investors survives although one of them sooner or later will dominate. In fact, this market selection is amplified when the number of assets is increased as shown by Fedyk et al (2013). 2 The immediate implication is that the economy eventually will approach a single-agent economy but as can be learned from the above papers the price impact can still be substantial.…”
Section: State Price Densities and Consumption Allocationsmentioning
confidence: 99%
“…, t t n t π π π ′ = ⋅⋅⋅ π t and 2 1 , 1 1, 1 (22) and (23) into (17), we have (24) Thus the first order condition of the problem (7) leads to the following optimal solution (25)…”
Section: The Demand Functionmentioning
confidence: 99%
“…Blume and Easley [1] associated market selection with the first-principle of welfare economics, and discovered that in complete market under Pareto optimum allocation, the survival and disappearance of investors depend on the accuracy of their forecasts. Similarly, Fedyk, Heyerdahl and Walden [2] studied the multi-asset economy situation and found that, compared with rational investors, unsophisticated investors could suffer severe loss in the long run even their predication deviations seem priori small. Barucci and Casna [3] also found that under the mean reverting environment, investors who have inaccuracy predictions cannot survive.…”
Section: Introductionmentioning
confidence: 99%